2023
DOI: 10.3390/membranes13040408
|View full text |Cite
|
Sign up to set email alerts
|

The Role of C2 Domains in Two Different Phosphatases: PTEN and SHIP2

Abstract: Phosphatase and tensin homologue (PTEN) and SH2-containing inositol 5′-phosphatase 2 (SHIP2) are structurally and functionally similar. They both consist of a phosphatase (Ptase) domain and an adjacent C2 domain, and both proteins dephosphorylate phosphoinositol-tri(3,4,5)phosphate, PI(3,4,5)P3; PTEN at the 3-phophate and SHIP2 at the 5-phosphate. Therefore, they play pivotal roles in the PI3K/Akt pathway. Here, we investigate the role of the C2 domain in membrane interactions of PTEN and SHIP2, using molecula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…More recent MD simulations ( John et al, 2023 ) with SHIP2 bound to a lipid membrane suggest that C2 causes conformational changes in L4 and α5–7, but there is no change in flexibility in these regions, which may be because that the presence of a lipid membrane changes protein conformational dynamics. Another study ( Le Coq et al, 2021 ) focusing on the function of the PHR domain of SHIP2 showed that the reaction product PI(3,4)P 2 induces higher activity of PHR-Ptase-C2 compared to Ptase-C2 and Ptase.…”
Section: C2 Domain-containing Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent MD simulations ( John et al, 2023 ) with SHIP2 bound to a lipid membrane suggest that C2 causes conformational changes in L4 and α5–7, but there is no change in flexibility in these regions, which may be because that the presence of a lipid membrane changes protein conformational dynamics. Another study ( Le Coq et al, 2021 ) focusing on the function of the PHR domain of SHIP2 showed that the reaction product PI(3,4)P 2 induces higher activity of PHR-Ptase-C2 compared to Ptase-C2 and Ptase.…”
Section: C2 Domain-containing Enzymesmentioning
confidence: 99%
“…A simulation and calculation work also compared the role of C2 domains in PTEN and SHIP2 ( John et al, 2023 ). This study showed that the C2 domain of PTEN plays an important role in membrane binding and adjusts the posture of PTEN for substrate binding which is similar to the role of other C2 domains.…”
Section: C2 Domain-containing Enzymesmentioning
confidence: 99%